Histamine Regulates the Inflammatory Profile of SOD1-G93A Microglia and the Histaminergic System Is Dysregulated in Amyotrophic Lateral Sclerosis - Apolloni, Savina; Fabbrizio, Paola; Amadio, Susanna; Napoli, Giulia; Verdile, Veronica; Morello, Giovanna; Iemmolo, Rosario; Aronica, Eleonora; Cavallaro, Sebastiano; Volonté, Cinzia (Frontiers in Immunology, 2017)
ABSTRACT Amyotrophic Lateral Sclerosis (ALS) is a late-onset motor neuron disease where activated glia release pro-inflammatory cytokines that trigger a vicious cycle of neurodegeneration in the absence of resolution of inflammation. Given the well-established role of histamine as a neuron-to-glia alarm signal implicated in brain disorders, the aim of this study was to investigate the expression and regulation of the histaminergic pathway in microglial activation in ALS mouse model and in humans. By examining the contribution of the histaminergic system to ALS, we found that particularly via H1 and H4 receptors, histamine promoted an anti-inflammatory profile in microglia from SOD1-G93A mice and modulated their activation state. A decrease in NF-B and NADPH oxidase 2 with an increase in arginase 1 and P2Y12 receptor was induced by histamine only in the ALS inflammatory environment, but not in the healthy microglia, together with an increase in IL-6, IL-10, CD163 and CD206 phenotypic markers in SOD1-G93A cells. Moreover, histaminergic H1, H2, H3 and H4 receptors, and histamine metabolizing enzymes histidine decarboxylase, histamine N-methyltransferase and diamine oxidase were found deregulated in spinal cord, cortex and hypothalamus of SOD1-G93A mice during disease progression. Finally, by performing a meta-analysis study, we found a modulated expression of histamine-related genes in cortex and spinal cord from sporadic ALS patients. Our findings disclose that histamine acts as anti-inflammatory agent in microglia and suggest a dysregulation of the histaminergic signaling in ALS.